Reviewer - Management, Journal of Infrastructure & Facility Asset (Journal of Infrastructure & Facility Asset Management, 2025)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.-          Papers must be a real work of the author.-          Papers has never been published in other media.-          Papers must contain discussion about Infrastructure & Facility Asset Management.-          Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.-          The paper has to take references from Scientific Journal with minimum of 5 papers.-          Paper lengths are limited in 8-16 pages.-          Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to,-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Policy-          I & F Planning-          I & F Administration Aspects-          I & F Operation System-          I & F Maintenance System-          I & F Evaluation Technique-          I & F Disposal-          I & F Economical Aspect-          I & F Financial Aspect-          I & F Management Organization-          I & F Spatial Aspects and Environmental AspectsReviewerProf. Dr. Ir. Ria Asih A. S. M.Eng, Institut Teknologi Sepuluh Nopember (ITS), SurabayaDr. Trihanyndio R. S. ST., MT., Institut Teknologi Sepuluh Nopember (ITS), Surabaya, IndonesiaDr. Mahendra A. M. ST., MT., Institut Teknologi Sepuluh Nopember (ITS), Surabaya, IndonesiaData Iranata ST., MT., Ph.D, Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, Surabaya, Indonesia.Dr. Ir. Alex Abdi Chalix MM., MT., Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, Surabaya, Indonesia.Prof. Dr.Tech.Ir. Danang Parikesit MSc., University Network For Indonesia Infrastructure Development, Indonesia.Prof.madya Dr. Maimunah Bt Sapri, Real Estate Department, Universiti Teknologi Malaysia, Johor Bahru, Malaysia.Wahyu Caesarendra, ST., M. Eng., Ph.D., Departement Integrated Technology, University Brunei Darussalam, Brunei Darussalam.